Continuous Fixed‐Time Controller Design for Dynamic Systems with Unmeasurable States Subject to Unbounded Disturbances - Basin, Michael; Avellaneda, Fernando Guerra (Asian journal of control, 2019)
This paper presents a nonlinear continuous observer‐based controller that provides fixed‐time convergence to the origin (a vicinity of the origin) of a higher‐order dynamic system subject to unbounded disturbances, whose only measurable state is the highest relative degree one. The settling time estimation problem is solved computing an uniform upper bound of the fixed convergence time of the designed controller. Finally, the designed algorithm is verified in a case study of an industrial armature‐controlled DC motor.